Development and evaluation of an intervention on suPpoRting infOrmal cAregivers of older people with early CogniTIVe declinE (PROACTIVE): a study protocol based on the Medical Research Council framework - Johanna de Almeida Mello; Anja Declercq (BMJ Open)
Introduction Caring for people with cognitive problems can have an impact on informal caregivers’ health and well-being, and especially increases pressure on healthcare systems due to an increasing ageing society. In response to a higher demand of informal care, evidence suggests that timely support for informal caregivers is essential. The New York University Caregiver Intervention (NYUCI) has proven consistent effectiveness and high adaptability over 30 years. This study has three main objectives: to develop and evaluate the Flemish adaptation of the NYUCI in the context of caregiving for older people with early cognitive decline; to explore the causal mechanism of changes in caregivers’ health and well-being and to evaluate the validity and feasibility of the interRAI Family Carer Needs Assessment in Flanders.Methods and analysis Guided by Medical Research Council framework, this study covers the development and evaluation phases of the adapted NYUCI, named PROACTIVE—suPpoRting infOrmal cAregivers of older people with early CogniTIVe declinE. In the development phase, we will identify the evidence base and prominent theory, and develop the PROACTIVE intervention in the Flemish context. In the evaluation phase, we will evaluate the PROACTIVE intervention with a pretest and posttest design in 1 year. Quantitative data will be collected with the BelRAI Screener, the BelRAI Social Supplement and the interRAI Family Carer Needs Assessment at baseline and follow-up points (at 4, 8 and 12 months). Qualitative data will be collected using counselling logs, evaluation forms and focus groups. Quantitative data and qualitative data will be analysed with SAS 9.4 software and NVivo software, respectively. Efficacy and process evaluation of the intervention will be performed.Ethics and dissemination This study has been approved by the Ethics Committee of KU Leuven with a dossier number G-2020-1771-R2(MAR). Findings will be disseminated through community information sessions, peer-reviewed publications and national and international conference presentations.